OPTIMIZATION OF THE QUALITY OF MEDICAL CARE FOR CHILDREN AFTER SURGICAL TREATMENT OF CONGENITAL HEART DEFECTS: CLINICAL AND ORGANIZATIONAL ASPECTS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Congenital heart defects (CHD) are one of the most common anomalies among newborns requiring surgical intervention. However, the success of the operation does not always guarantee an optimal outcome if high-quality postoperative care is not provided. The article discusses aspects of optimizing medical care for children after surgical treatment of CHD, including organizational and clinical problems, modern methods of diagnosis and treatment, as well as rehabilitation. Key organizational aspects, such as a multidisciplinary approach, the role of telemedicine and the need to improve the skills of medical workers are described. Particular attention is paid to the issues of financing and accessibility of medical services. To improve the quality of medical care, recommendations are proposed aimed at developing the healthcare infrastructure and improving the level of professional training of specialists.